Validated prediction of xerostomia in a real-world population: a step toward model-guided radiotherapy - Emmy Dalqvist; Tiziana Rancati; Anna Embring; Gabriella Alexandersson von Döbeln; Ingmar Lax; Signe Friesland; Eva Onjukka (Acta Oncologica)
Background and purpose: The aim of this study is to validate an Normal Tissue Complication Probability (NTCP) model for xerostomia in a large quality-registry cohort, enabling its future use in individualized NTCP-based treatment planning.